FEATURES PATHOMORPHOLOGICAL MANIFESTATIONS OF DYSPLASTIC CHANGES OF VARIOUS DEGREES IN THE CERVIX IN WOMEN OF DIFFERENT AGE GROUPS - M. S. Seliakova; T. A. Ageeva (Сибирский онкологический журнал, 2016)
Morphological and morphometric study of biopsy showed that in the 2 age groups of subjects: 1 – 65 women of reproductive age to 35 years old, 2 – 57 women postreproductive age, over 49 years. Patients of the 1-st group were more frequent CIN2 and CIN3. It is revealed that the patients of this group in the stratified squamous epithelium of the cervix are more active processes of proliferation, expressed as a thickening layer of stratified squamous epithelium on the whole, the thickening of the basal layer, more common acanthosis, in comparison with changes of stratified squamous epithelium in women of older age. It is established that the symptoms of viral lesions of the stratified squamous epithelium (koilocytes), often encountered in young women. Assessment of the manifestations of the reaction of local immunity in the stroma of the cervix showed that more severe inflammatory reaction was marked in young patients with CIN3 as the most active perifocal inflammatory process.